Controllable preparation of one-dimensional Li1.2Mn0.54Ni0.13Co0.13O2 cathode materials for high-performance lithium-ion batteries. Issue 9 (26th January 2021) - Gao, Zhi; Zhao, Jiayi; Pan, Xiaoliang; Liu, Lijun; Xie, Shikun; Yuan, Huiling
Abstract : Li1.2 Mn0.54 Ni0.13 Co0.13 O2 rods with controllable sizes were synthesized via a co-precipitation route followed by a post-calcination treatment to improve rate capabilities. Abstract : Lithium-rich layered oxides are attractive candidates of high-energy-density cathode materials for high-performance lithium ion batteries because of their high specific capacity and low cost. Nevertheless, their unsatisfactory rate capability and poor cycling stability have strongly hindered commercial applications in lithium ion batteries, mainly due to the ineffectiveness of the complicated synthesis techniques to control their morphologies and sizes. In this work, the Li1.2 Mn0.54 Ni0.13 Co0.13 O2 cathode materials with a one-dimensional rod-like morphology were synthesized via a facile co-precipitation route followed by a post-calcination treatment. By reasonably adding NH3 ·H2 O in the co-precipitation reaction, the sizes of the metal oxalate precursors could be rationally varied. The electrochemical measurements displayed that the Li1.2 Mn0.54 Ni0.13 Co0.13 O2 short rods delivered a high capacity of 286 mA h g −1 at 0.1C and excellent capacity retention of 85% after 100 cycles, which could be contributed to the improvement of the electrolyte contact, Li + diffusion, and structural stability of the one-dimension porous structure.